Русские экклезионимы (на материале Географическо-статистического словаря Российской империи П. П. Семенова-Тян-Шанского) - Janik-Borecka, Katarzyna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
This article shows the analysis of ecclesionyms extracted from the first volume of the five-volume Geographical-statistical dictionary of the Russian Empire by P. P. Semyonov-Tyan-Shansky. This text aims to presents the term ecclesionym as one of toponyms. The following three classifications have been suggested: 1) classification involving the key word indicating the type of the temple, 2) classification involving a descriptive component, 3) motivational classification.